PENGARUH MEDIA PEMBELAJARAN GAME INTERAKTIF TERHADAP KECERDASAN EMOSIONAL PADA MATERI SUHU DAN KALOR KELAS V SEKOLAH DASAR - Ropita Sari; Sukardi; Aldora Pratama (STKIP Subang, 2023)
The formulation of the research problem is whether there is an influence of interactive game learning media on emotional intelligence in the subject of temperature and heat in grade V elementary school? This study aims to determine the effect of interactive game learning on emotional intelligence in the material temperature and heat class V Elementary School. This research was conducted in the even semester of the 2023/2024 academic year. The method used in this research is the pre-experimental method with a one group pretest-posttest design. The research sample consisted of one class of 30 students. The research instrument used was a questionnaire of 20 questions, while the data analysis technique used the t test. Based on the results of the study it was found that the average pretest value questionnaire produced was 66,30 and the posttest questionnaire average was 78,47. Thus, it can be concluded that interactive game learning media has an effect on emotional intelligence in the subject of temperature and heat in class V of elementary school.